[PP.11.16] THE COMBINATION DRUG VALSARTAN/SACUBITRIL (LCZ696) REDUCED PULSE WAVE VELOCITY AND AORTIC SYSTOLIC BLOOD PRESSURE IN PATIENTS WITH HEART FAILURE WITH REDUCED EJECTION FRACTION. (September 2016) - Kobalava, Z.; Babaeva, L.; Lukina, O.; Zharikova, E.; Tyukhmenev, E.; Villevalde, S.
Abstract : Objective: Dual neprilysin inhibition and angiotensin receptor blockade with LCZ696 has been shown therapeutic benefits in chronic heart failure (CHF) patients. The aim of the study was to assess LCZ696 effects on parameters of arterial stiffness in stable heart failure with reduced ejection fraction (HFrEF). Design and method: In the open-label follow-up to PARADIGM HF study 18 patients with stable HFrEF (16 male, 69 ± 9 years (M ± SD), arterial hypertension 83%, previous myocardial infarction 89%, diabetes mellitus 39%, dyslipidemia 56%, LVEF 32 ± 4%, serum creatinine 118 ± 21 μmol/l, eGFR 56 ± 13 ml/min/1.73m2, potassium 4.45 ± 0.35 mmol/l) were enrolled. Patients received a stable background treatment for at least a month (ACEI 94%, beta-blockers 100%, aldosterone receptor antagonists 83.3%, loop diuretics 72.2%). ACEI treatment was interrupted for 36 h and replaced with LCZ696 100 or 200 mg (11 patients) BID according to baseline brachial BP (mean dose 185.7 ± 36.3 mg BID). Applanation tonometry was performed baseline and after 6 month LCZ696 therapy. Wilcoxon test was considered significant if p < 0.05. Results: Baseline brachial BP decreased from 137.1 ± 22.0/83.4 ± 11.8 to 120.5 ± 13.5/75.1 ± 9.3 mmHg (δ −16.6 ± 14.2/−8.3 ± 10.3 mmHg, p < 0.05), heart rate did not change (78 ± 12 vs 75 ± 15 beats/min (δ −2.7 ± 14.7 beats/min, p > 0.05). Valsartan/sacubitril therapy was associated with significant decrease of carotid-femoral pulse wave velocity (11.5 ± 2.9 vs 10.2 ± 2.9 m/s, p < 0.05), central systolic (125 ± 16 vs 116 ± 15 mmHg, p = 0.005) and diastolic (78 ± 7 vs 74 ± 9 mmHg, p < 0.05) blood pressure. Central pulse pressure (45 ± 11 vs 41 ± 16 mmHg), augmentation pressure (16 ± 7, 1 vs 13, 8 ± 8, 4 mmHg), augmentation index (29 ± 7 vs 28 ± 11%), time to reflected wave (128 ± 8 vs 132 ± 7 ms) did not change significantly (p > 0.05 for all comparisons). Conclusions: In stable patients with heart failure with reduced ejection fraction 6 month valsartan/sacubitril therapy was associated with significant decrease of aortic systolic pressure and pulse wave velocity.